2018
DOI: 10.2478/rjr-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microbial etiology in acute and chronic rhinosinusitis and its role in the current management of antibiotic treatment

Abstract: BACKGROUND. Acute and chronic rhinosinusitis (CRS) are common conditions worldwide. In most cases, the etiology of acute rhinosinusitis (ARS) is viral, but there can be cases complicated by bacterial infection. The bacterial pathogens responsible for acute bacterial rhinosinusitis (ABRS) in most cases are Streptococcus pneumoniae, Haemophilus influenza and Moraxella catarrhalis. In recent years, some changes regarding this issue have been communicated. Also, the pathophysiology of CRS becomes a problem due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Based on the data in table 3, the majority of rhinosinusitis patients at the Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Clinic of Universitas Airlangga Hospital were diagnosed with chronic rhinosinusitis, with a disease duration of ≥12 weeks, constituting 80.5%. Several studies have shown similar results, indicating a higher prevalence of chronic rhinosinusitis compared to acute rhinosinusitis [5][17][15] [18]. The factor of insufficient knowledge and awareness levels among the community in recognizing the symptoms of rhinosinusitis, coupled with the perception that these symptoms are common and will disappear with inappropriate medication, may lead to recurring incidents resulting in severe symptoms and the development of chronic conditions [19].…”
Section: Discussionmentioning
confidence: 96%
“…Based on the data in table 3, the majority of rhinosinusitis patients at the Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Clinic of Universitas Airlangga Hospital were diagnosed with chronic rhinosinusitis, with a disease duration of ≥12 weeks, constituting 80.5%. Several studies have shown similar results, indicating a higher prevalence of chronic rhinosinusitis compared to acute rhinosinusitis [5][17][15] [18]. The factor of insufficient knowledge and awareness levels among the community in recognizing the symptoms of rhinosinusitis, coupled with the perception that these symptoms are common and will disappear with inappropriate medication, may lead to recurring incidents resulting in severe symptoms and the development of chronic conditions [19].…”
Section: Discussionmentioning
confidence: 96%
“…13 Di Romania, 50% penderita KNF terdiagnosis pada stadium lanjut yaitu 33,33% pada stadium IV (27,78% IVA, 5,57% IVB) dan 16,66% pada stadium III. 12 Stadium KNF berhubungan dengan dengan angka kelangsungan hidup 5 tahun. Menurut Esam, 21 angka kelangsungan hidup 5 tahun pada stadium I 100%, stadium II 93,3%, stadium III 62,7%, stadium IVA 42,2%, dan stadium IVB 40,6%.…”
Section: Diskusiunclassified